Development of generic wireless channel simulator for diverse environment - Mamat, Nor Aswani (2012)
The development of generic wireless channel simulator is proposed in this work. This simulator is based on the time-scale domain generalized eigenstructure for all wireless propagation channels and developed in LabVIEW®. It is envisaged that such simulator will be able to serve as all-in-one system for the evaluation of the channel characteristics and transceiver performance for almost all contemporary communication channels and systems.